Effects of Antioxidants Resveratrol, Catechin and Lipoic Acid and Carcinogen KBrO3 on Lipophylic Vitamins and Cholesterol in Lung, Liver and Kidney of Wistar Rats - Keser, Serhat; Yilmaz, Okkes; Tuzcu, Mehmet; Erman, Orhan; Irtegun, Sevgi (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
The aim of this research is to examine effects of antioxidants resveratrol, lipoic acid, catechin and carcinogen potassium bromate on the level of lipophylic vitamins and cholesterol in liver, lung and kidney tissue of Wistar albino rats. In this study, total 50 Wistar rats were randomly divided into five groups: 1. Control (C), 2. KBrO3 (K) (40 mg/kg two times per week), 3. Catechin (30 mg/kg four times per week) + KBrO3 (40 mg/kg two times per week) (Cat), 4. Lipoic Acid (30 mg/kg four times per week) + KBrO3 (40 mg/kg two times per week) (LA) and 5. Resveratrol (30 mg/kg four times per week) + KBrO3 (40 mg/kg two times per week) (R). All treatments were continued for 5 weeks, after which time each experimental rat was decapitated and tissues were collected and stored in -85 degrees C prior to biochemical analysis. In lung, liver and kidney, lipophylic vitamins and cholesterol were measured by HPLC. According to our results, while the cholesterol level was decreased in the K, Cat, LA and R groups, the alpha-tocopherol level was decreased in K and R groups of the lung tissue. alpha-tocopherol, cholesterol and retinol levels were increased in K, Cat, LA and R groups of the liver tissue. While the delta-tocopherol, vitamin D-2, vitamin D-3 and alpha-tocopherol levels were decreased in K, Cat, LA and R groups, the cholesterol level was increased in Cat, LA and R groups of kidney tissue. In conclusion, our results indicated that the applications of resveratrol, lipoic acid, catechin and potassium bromate influenced cholesterol and lipophylic vitamins levels and these applications can be affected cholesterol biosynthesis in Wistar albino rats.
Wistar sıçanların akci?er, karaci?er ve böbrek dokularında lipofilik vitaminler ve kolesterol üzerinde antioksidanlar resveratrol, kateşin ve lipoik asit ile kanserojen KBrO 3'ın etkileri
Keywords: Resveratrol; Potassium bromate; Catechin; Lipoic acid; Liver; Lung; Kidney